Uso de fosfitos para o controle de Sclerotinia sclerotiorum e Sclerotium rolfsii in vitro - (:unkn) unknown (Universidade Federal do Pampa, 2015)
Diseases such as white mold and rot by sclerotia, caused by Sclerotinia sclerotiorum and Sclerotium rolfsii, respectively, are considered severe nature, covering hundreds of host crops of economic importance, being responsible for major losses in agricultural production worldwide. However, no single control method is effective and long term use of fungicides can result in new races of pathogens. In this sense, the objective of this study was to evaluate the efficiency of phosphite fungitoxic testing and production of sclerotia in vitro to fungi S. sclerotiorum and S. rolfsii. The experiments were set up in completely randomized design, with six treatments and five replications for each fungus, and the experimental unit consisting of a Petri dish. 5 mm mycelial discs were used for each fungus, from four days of growth colonies. The disks were transferred to petri dishes containing PDA (potato dextrose agar) and added the following treatments: 3 mL L-¹ Reforce® (potassium phosphite), 5 mL L-¹ of Reforce Cu® (potassium phosphite + copper), 3 mL L-¹ Reforce Zn® (zinc phosphite), 3 mL L-¹ of Yantra® (potassium phosphite) and 5 mL L-¹ of Fulland® (copper phosphite), kept in climate-controlled chamber at 25°C and photoperiod of 12 hours for 4 days. They evaluated the mycelial growth rate index (MIGS) according to the average of the colony diameter, measured in 24-h intervals. For the fungus S. rolfsii was recorded the number of sclerotia after 15 days. The data were submitted to ANOVA and Tukey test average of 5%. The Enforce Zn® treatment showed over 95% control of the fungus S. sclerotiorum MIGS, while for the fungus S. rolfsii showed 93%. Even after 15 days there was no production of sclerotia for the treatment Reforce Zn® . After confirmed the fungistatic action of phosphite Reforce Zn® the doses tested were 0 (control), 2, 4, 6 and 8 mL L-¹, and the later submitted data regression analysis. It was observed that doses higher than 4 mL inhibiting the mycelial growth of both fungi. Considering the results, it is concluded that zinc phosphite can be an alternative way to control S. sclerotiorum and S. rolfsii.
Keywords: Controle alternativo; Fertilizante foliar; Ação fungistática; Alternative control; Foliar fertilizer; Fungistatic action; CNPQ::CIENCIAS AGRARIAS